HASIL BELAJAR SISWA SMA MELALUI MODEL PEMBELAJARAN TIME TOKEN DAN SNOWBALL THROWING PADA TOPIK PELESTARIAN LINGKUNGAN - Yossie Ulfa Nuzalifa; Dini Annisha (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2021)
The cooperative learning process using Time Token and Snowball Throwing on Environmental Conservation material at Istiqlal Delitua High School implements real and scientific learning activities supported by students general knowledge covering environmental problems and describing concern for these problems. This study aims to determine the comparison of student learning outcomes taught using the learning models Time Token and Snowball Throwing. The research design used in this study is a quasiexperimental study with the method, Simple Random Sampling namely: a) 36 students of class X-2 as the experimental class I using the model Time Token and b) 36 students of class X-3 as the experimental class II using model Snowball Throwing. The results showed that the mean score of students with learning Time Token was higher, namely 80.61, while the average score of students with learning was Snowball Throwing 76.72. Based on these averages It can be concluded that there is a significant difference between student learning outcomes using the model Time Token and Snowball Throwing. Model pembelajaran Time Token dan Snowball Throwing digunakan di kelas X SMA Istiqlal Delitua pada topik Pelestarian Lingkungan yang mencakup materi permasalahan lingkungan dan kepedulian lingkungan melalui aktivitas kontekstual dan ilmiah . Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar siswa yang diajarkan dengan menggunakan model Time Token dan Snowball Throwing. Desain penelitian yang digunakan pada penelitian ini, yaitu kuasi eksperimen dengan metode Simple Random Sampling yaitu : a) 36 siswa kelas X-2 sebagai kelas eksperimen I yang menggunakan model Time Token dan b) 36 orang siswa kelas X-3 sebagai kelas eksperimen II yang menggunakan model Snowball Throwing. Hasil penelitian menunjukkan bahwa nilai rata-rata siswa dengan pembelajaran Time Token lebih tinggi yaitu 80,61 sedangkan nilai rata-rata siswa dengan pembelajaran Snowball Throwing yaitu 76,72. Berdasarkan rerata tersebut dapat disimpulkan bahwa terdapat perbedaan yang signifikan antara hasil belajar siswa yang menggunakan model Time Token dan Snowball Throwing.